Descriptive Quantitative Analysis Of The Influence Of Digital Spt On Taxpayer Compliance - Hapsari, Nora (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2021)
The government needs to act pro-actively, namely making real efforts to increase public awareness of paying taxes, including by innovating digital tax services. The existence of a digital SPT is expected to be a positive signal for increasing public participation in paying taxes. The research method is descriptive quantitative, which is to analyze respondents' answers to a number of questions related to digital SPT and tax compliance. There are 100 units of analysis registered as taxpayers at the Tanah Abang 2 tax office, Central Jakarta. The results of the study state that digital SPT has an impact of 0.632 on awareness of paying taxes. This implies that digital innovation in the field of taxation is a real step that the public has responded positively, so that the tax participation rate has increased drastically.